SELF-CARE TRAINING FOR SANTRI AS AN EFFORT TO PREVENT SCABIES IN PESANTREN - Khamida; Fitriasari, Andikawati; Widyaswari, Meidyta Sinantryana (Community Service Journal of Indonesia, 2024)
Islamic boarding schools in Indonesia have classic problems related to the health of students, one of which is common in Islamic boarding schools and identical to the lives of students, is scabies. This community service activity was carried out at the As Syafiiyah Islamic boarding school to provide solutions to the problems of the As Syafiiyah Islamic boarding school community by providing education, training as well and mentoring Islamic boarding school health cadres in preventing scabies. This activity is carried out by providing education, training, and assistance to students and poskestren cadres about "self-care" in preventing scabies. Evaluation of this activity was carried out using pre and post-test scores. It was found that there was an increase in the post-test score compared to the pre-test. Before the self-care training was given, it was found that 20% of the students were still not clean in maintaining their hygiene, but after the self-care training was given, it was found that none (0%) of the students were clean and 58.5% of their hygiene was good. It is concluded that self-care training can improve the ability of students to prevent scabies through personal hygiene skills which include: clothing hygiene, skin hygiene, hand and nail hygiene, genital hygiene, towel hygiene, and cleanliness of prayer tools. The behavior of preventing scabies through maintaining personal hygiene needs to be stated in the Pesantren regulations and socialized to the Pesantren community and requires support from the Kyai or Pesantren leaders, including Bu Nyai Pesantren so that it can be implemented properly.